The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22137032
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Contributes to Enhanced Platelet Activation in Patients with Type 1 Diabetes Mellitus

Abstract: Atherosclerotic cardiovascular disease is the major cause of morbidity and mortality in patients with type 1 diabetes mellitus (T1DM). Enhanced platelet reactivity is considered a main determinant of the increased atherothrombotic risk of diabetic patients. Thrombopoietin (THPO), a humoral growth factor able to stimulate megakaryocyte proliferation and differentiation, also modulates the response of mature platelets by enhancing both activation and binding to leukocytes in response to different agonists. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Hyperglycemia induces secretion of TPO that potentiates agonist-induced activation of mature platelets. Levels positively correlate with blood glucose and level of control HbA1C [17].…”
Section: Hyperglycemiamentioning
confidence: 89%
See 2 more Smart Citations
“…Hyperglycemia induces secretion of TPO that potentiates agonist-induced activation of mature platelets. Levels positively correlate with blood glucose and level of control HbA1C [17].…”
Section: Hyperglycemiamentioning
confidence: 89%
“…In DM, the hyperglycemia acts through neutrophils to stimulate thrombopoietin (TPO) production in the liver and enhance megakaryocyte thrombopoiesis [16]. In T1DM, increased circulating TPO has been shown to be linked to elevated blood sugar levels and HbA1c HbA1C [17] providing evidence linking bone marrow megakaryopoiesis and metabolic state.…”
Section: Bone Marrow and Megakaryocytes In T1dmmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that enhanced PLT reactivity is considered a main determinant of the increased atherothrombotic risk of diabetic patients. Thrombopoietin, a humoral growth factor able to stimulate megakaryocyte proliferation and differentiation, also modulates the response of mature PLT by enhancing both activation and binding to leukocytes in response to different agonists ( 31 ). Cluster I in the DN group was found to have a somewhat increased PLT count, high frequency of DKA episodes/year, high MAU, prominent increase in HIF level, and prominent disturbances in apoptosis controlling factors BcL-xL and caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The phenomenon of COVID-19 platelet activation is likely due to the association between inflammation/infection and platelet production. Platelet production and activation is driven by thrombopoietin, 9,10 which is upregulated by inflammatory cytokines activated in COVID-19 infection, such as interleukin-6. Platelets also possess cell surface receptors that contribute to immune cell interaction and function.…”
mentioning
confidence: 99%